An investigation into the effects of Selective Serotonin Reuptake Inhibitor (SSRI) antidepressants on sperm parameters - an in vitro study - Krausey, Gemma Eden (Stellenbosch : Stellenbosch University, 2025)
Krausey, G. E. 2025. An investigation into the effects of Selective Serotonin Reuptake Inhibitor (SSRI) antidepressants on sperm parameters - an in vitro study. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/85715747-dfca-49d3-be4d-dd6645dd3816